(untitled) (Journal of the College of Basic Education, 2022)
E-learning systems have been adopting the blended learning approach because blended learning systems have the advantages of e-learning (flexibility in time and location, adaption to particular user needs) without its disadvantages (teacher- student relationship broken, isolation feeling in front of the computer. The use of blended learning systems has still not spread to all educational institutions, largely because of issues of its own. It is not just that teachers and students need to adapt to new computer technology. The use of blended learning program might be rejected simply because of technological challenges, if not all teachers and students can be assumed to have necessary technological skills to use the software. This could be why the uptake of blended learning systems has been strongest in computer science department. Our proposed system detailing with designed simulation blended learning systems so that they are easy to use for people without any technical training, and thus to lessen the rejection of blended learning programs for this reason. And our proposed system can operate effectively with the content of the course being delivered by teachers through lectures while the online component is used by the student to review the content after class.